The Comparative Analysis of Students' Needs of SMA, SMK & MA Al-Ittihad DDI Soni (Students' and Teachers' Perspectives) - Nahdawati; Rahmatul Ummu Arifin; Sitti Hawaena; Murniati; Moh Jusri Kahar (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study aims to analyze and compare the English learning needs from the perspectives of students and teachers at SMKN 1 Dampal Selatan, MA Al-Ittihad DDI Soni, and SMA Negeri 1 Dampal Selatan. The research employs a qualitative descriptive approach using data collected through questionnaires distributed to students and interviews conducted with English teachers. The focus of this study includes academic needs such as mastery of the four main English skills, and non-academic needs like motivation, environmental support, and self-confidence, as well as perceptions regarding the use of technology in learning. The results indicate a significant gap between students’ and teachers’ expectations. Students tend to prefer practical, technology-based, and work-oriented materials, while teachers emphasize grammar mastery, basic language skills, and the need for adequate learning media. Additionally, students expressed difficulties in vocabulary acquisition and low confidence in speaking, whereas teachers stressed the importance of enhancing motivation and learning facilities. These findings highlight the necessity to adjust curricula and teaching methods to better align with students’ real-world needs and support more effective English learning.